PELAKSANAAN EKSTRAKURIKULER DI SMP N 1 PAYAKUMBUH - Wina Priyanti; Jagar Lumban Toruan; Yos Sudarman (FBS Universitas Negeri Padang, 2014)
Abstract The research was about the implementation of extracurricular activities at SMP N 1 Payakumbuh. The problem in the research was the fact thet students’ achievements in their curricular and in their extracurricular activities were unbalance. The research aimed at describing the implementation of extracurricular activities at SMP N 1 Payakumbuh. The design of the research was qualitative using descriptive analysis method. Students’ achievement in extracurricular activities was an efford done to maintain the good reputation of the school. Yet, there were problem faced by the students such as the decreasing of the result in few subjects. Thus, it was concluded that extracurricular activities at SMP N 1 Payakumbuh was demanded as one school with a good reputation. Keyword: implementation, extracurricular, reputation, Payakumbuh